Do Economic Growth, Income Distribution, and Investment Reduce Poverty Level? - Suwandi; Wardihan Sabar (Bulletin of Economic Studies (BEST), 2022)
Poverty is a condition of the population's inability to meet a decent standard of living. Poverty is also a measure of success in the development of a country or region. This study proposes a hypothesis where economic growth, income distribution, and investment are considered to have a large enough impact on reducing poverty in Enrekang Regency. The data used in this study is secondary data in the form of time series data for the period 2011-2020. The data analysis technique used multiple linear regression analysis. The results of this study indicate that economic growth and income distribution have no significant effect on the poverty level in Enrekang Regency. Meanwhile, investment has a significant negative effect on the poverty level in Enrekang Regency, which means that an increase in multisectoral investment can reduce poverty in this region. So that one of the important things in this study is the hope that the level of labor-intensive investment in Enrekang Regency can continue to be increased in various economic sectors.